Triboacoustic localization for mobile device: Improving accuracy & noise clustering - Leong Y.W.; Seki H.; Kamiya Y.; Hikizu M. (Fuji Technology Press, 2023)
Gradient methods; Gradient Descent method; Input methods; Inverse relationship; Noise clustering; Noise interference; Noise segregator; Sound source segregation; Triboacoustics; Inverse problems